EL software educativo un recurso didáctico empleado por el docente en el proceso enseñanza-aprendizaje de la factorización con números reales del bloque curricular de relaciones y funciones y su incidencia en el desarrollo de destrezas con criterio de desempeño de los estudiantes del noveno año de educación general básica de la unidad educativa anexa a la UNL, del barrio La Argelia, parroquia San Sebastián, de la ciudad, cantón y provincia de Loja, periodo 2012-2013, lineamientos alternativos - Beltran Corodva, Stefany Andreina (2014)
This research work refers to the following problema: ¿The educational software as didactic resource used by the profesor in the teaching-learning process strikes in the development of skills with performance criterio of the factorization inside the real numbers of fuctions and relations of curricular block, in the student of ninth year of Basic General Education of the Educational Unity annexed to the National University of Loja, period 2012-2013. The specific objectives that guide the present research work are:  To determine the knowledge level of professor about educational software as didactic resource in teaching – learning process of the factorization, strikes in the development of skill with performance criteria of the students of ninth year of Basic General Education.  To stablish if the use of educational software as didactic resource of professors in the teaching learning process of the factorization inside the real numbers, strikes in the development of skills with performance criteria of the students of ninth year of Basic General Education.  To elaborate an alternative program about the use of the educational software to improve the development of skills with performance criteria in the factorization inside the curricular block of functions and relations in the students if ninth year Basic General Education of the educational unity annexed to the National University of Loja. The results determined that both teachers and students have a minimum level of knowledge about educational software, which shows notoriously that in the institution leaves aside the teachers' updating regarding the use of didactic resources through new technologies. In the same way it can deduce that educational software as a didactic resource is not used by teachers in the teaching-learning process of the factorization of real numbers, which limits the interaction of the students with these types of computing resources, preventing these students obtain the advantages that these resources offer such as to strengthen knowledge and make a more active and motivating class, thus causing a lacking skill development with performance criteria.